Learning Participation of Learners in Athletic Materials at SMP Negeri 1 Halong - Maris, Rizky Syawaldi; Amirudin, Akhmad; Arifin, Ramadhan (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the level of student learning participation in athletic materials at SMP Negeri 1 Halong. This study uses a quantitative descriptive method. The research population is 41 students in the 8th grade of SMP Negeri 1 Halong. The sampling technique used purposive sampling with a sample of 25 students. The instrument used is a questionnaire with a Likert scale that has been validated by experts. Data analysis uses percentage descriptive statistics to determine the level of student participation. The results showed that 9 students were 36% in the